Meningkatkan Hasil Belajar Matematika Melalui Penerapan Model Pembelajaran Jigsaw Pada Siswa Kelas V SDN Baros 3 Kota Sukabumi - Hasanah, Aan (utile: Jurnal Kependidikan, 2019)
Improving Mathematics Learning Outcomes Through Application of Jigsaw Learning Model In Grade V Students SDN Baros 3 Sukabumi City. Research with a classroom action research approach is carried out collaboratively and two cycles. The main purpose of this research is to know the improvement of learning result of grade V students of SDN Baros 3 Kota Sukabumi in Mathematics subject with Jigsaw learning model implementation. The research was conducted at SDN Baros 3 of Sukabumi City which was conducted in the first semester of September 2011. The subjects of this study were teachers, and grade 5 students of SDN Baros 3 Kota Sukabumi were 33 students. The results showed that the average value of learning outcomes in the first cycle I meeting that reached 51.51% completeness with an average value of 63.33 then increased in cycle I meeting II which reaches completeness 81.81% with an average value of 66.06 Then increase again in cycle II which reached 93.93% completeness with an average score of 70.33. This research concludes that the application of Jigsaw learning model can improve mathematics learning outcomes of grade V students SDN Baros 3 Sukabumi City In addition, the application of this learning model can improve the speed, participation, cooperation and accuracy of students in the learning process.